Effect of pulsed electrostatic fields on mass transfer in a modified Lewis cell - Assmann, Simon; Ibana, Don; McRae, C. (Gecamin Ltda, 2011)
Electrostatic solvent extraction (ESX) promises to circumvent many of the weaknesses of the current solvent extraction (SX) technology, but commercial application of the technique has not been achieved. This is partly owing to insufficient fundamental understanding of the technique particularly in regards to mass transfer. The present study investigated the influence of pulsed electrostatic fields on the mass transfer of cobalt into Cyanex 272 using a modified Lewis cell. This technique allows the measurement and observation of mass transfer across a flat liquid-liquid interface. The results showed that the application of pulsed electrostatic fields, either full-wave rectified (FWR) or half-wave rectified (HWR), enhances or retards the rate of mass transfer of cobalt (II) into Cyanex 272 owing to electrostatic attractive or repulsive forces. This field-induced enhancement or retardation of mass transfer occurs in both the aqueous and organic phases. Between the two types of fields, HWR yielded a much higher enhancement of mass transfer as the formation of an electrical double layer is minimised.